How information about race-based health disparities affects policy preferences: Evidence from a survey experiment about the COVID-19 pandemic in the United States. (May 2021) - Harell, Allison; Lieberman, Evan
Abstract: In this article, we report on the results of an experimental study to estimate the effects of delivering information about racial disparities in COVID-19-related death rates. On the one hand, we find that such information led to increased perception of risk among those Black respondents who lacked prior knowledge; and to increased support for a more concerted public health response among those White respondents who expressed favorable views towards Blacks at baseline. On the other hand, for Whites with colder views towards Blacks, the informational treatment had the opposite effect: it led to decreased risk perception and to lower levels of support for an aggressive response. Our findings highlight that well-intentioned public health campaigns spotlighting disparities might have adverse side effects and those ought to be considered as part of a broader strategy. The study contributes to a larger scholarly literature on the challenges of making and implementing social policy in racially-divided societies. Highlights: Disseminating information on racial disparities in COVID deaths had mixed effects. Filling informationals voids led to increased risk perception among Black Americans. Among Whites, attitudes towards Blacks moderated the effects of information. Support for COVID policy is a function of strength of attachment to those affected.